2017
DOI: 10.1097/cin.0000000000000335
|View full text |Cite
|
Sign up to set email alerts
|

Nurses’ Use and Perception of an Information and Communication Technology System for Improving Coordination During Hospital Discharges

Abstract: To facilitate communications between care levels and improve coordination during hospital discharges, there is great potential in using information and communication technology systems, because they can significantly help to deter unnecessary readmissions. However, there is still a lack of knowledge about how often nurses use information and communication technology and the indicators related to its use. The aims of this study were to describe the indicators related to nurses' use of an information and communi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 14 publications
1
5
0
Order By: Relevance
“…Self-confidence and perceived ease of use can increase CISs acceptance (Aldosari et al, 2018). Training can increase nurses' self-esteem in working with these systems (Christiansen et al, 2017). A variety of factors such as demographic characteristics (Aldosari et al, 2018), organizational factors, software performance and speed, motivation (Staudinger et al, 2007), information quality, senior management support and organizational factors can impact the acceptance of CISs in nursing practice.…”
Section: Discussionmentioning
confidence: 99%
“…Self-confidence and perceived ease of use can increase CISs acceptance (Aldosari et al, 2018). Training can increase nurses' self-esteem in working with these systems (Christiansen et al, 2017). A variety of factors such as demographic characteristics (Aldosari et al, 2018), organizational factors, software performance and speed, motivation (Staudinger et al, 2007), information quality, senior management support and organizational factors can impact the acceptance of CISs in nursing practice.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding correlation between nurses' total level of perception and their total reported practices, the current study revealed that there is positive correlation between nurses' total level of perception and their total reported practices This result is in agreement with Jannah, et al, (2019) (29) that conducted a study entitled "Discharge planning model with approach of method in improving patients' readiness for discharge in hospitals" and found that there is positive correlation between nurses' total level of perception and their total practices. Conversely, this this result is in disagreement with Christiansen, et al, (2017) (30) that conducted a study entitled "Nurses' use and perception of an information and communication technology system for improving coordination during hospital discharges" and found that there is negative correlation between nurses' total level of perception and their total practices.…”
Section: Discussionmentioning
confidence: 74%
“…Even with the adequate reliability coefficient, no overall total score for the positive and negative scales was computed, which would allow for different statistical approaches. Nurses' use and perception of technology has been measured by others using qualitative interviews (Sirois et al, 2013;Tunlind et al, 2015), focus groups (Romare et al, 2018), an investigator-developed questionnaire (Christiansen et al, 2017) with primarily dichotomous responses and no reported reliability or validity, and the early questionnaire with psychometric data from a sample in 11 countries by Arthur et al (1999) that has been adapted and used by others (Bagherian et al, 2017;Noh et al, 2002).…”
Section: Psychometrics Of Nurses' Perceptions Of Technology Effectiveness Scalementioning
confidence: 99%